Gazdasági növekedési potenciál és növekedési stratégiák - Morita, Tusneo (Marketing & Menedzsment, 2019)
How should the growth potential of Central European economies be assessed during the process of structural change? We believe that the determination of medium-term growth in Central European economies will require the consideration of special factors. Such factors will be identified to project the medium and long-term economic growth of Hungary.